Complementary resistive switching of annealed Ti/Cu2O/Ti stacks. (15th March 2016) - Wang, Hao-Yu; Jou, Shyankay; Huang, Bohr-Ran; Song, Wan-Jhen; Mao, Tzu-Zing
Abstract: Ti/Cu2 O/Ti stacks with 25-nm-thick Cu2 O layers were produced by sputter deposition and lift-off processes utilizing three photolithographic masks. Subsequent annealing of the Ti/Cu2 O/Ti stacks at 250 °C in a vacuum induced interfacial reactions between the Ti and Cu2 O layers and converted the Ti/Cu2 O/Ti stacks to a Ti/TiO x /Cu/TiO x /Ti structure. This pentalayered stack resembled a pair of antiserial Ti/TiO x /Cu and Cu/TiO x /Ti resistive switching devices and, therefore, demonstrated complementary resistive switching behaviors.